A new Opisthotropis Günther, 1872 (Colubridae: Natricinae) from northern Laos allied to the enigmatic Opisthotropis maculosa Stuart & Chuaynkern, 2007 - Stuart, Bryan L.; Seateun, Sengvilay; Chuaynkern, Yodchaiy; Ren, Jin-Long; Bernstein, Justin M.; Phimmachak, Somphouthone (Zootaxa, 2026)
The natricid snake genus Opisthotropis contains approximately 25 species distributed across tropical Asia. Three specimens of a distinctively patterned Opisthotropis from the Phou Katha Platea in Hom District, Xaysomboun Province, northern Laos, are shown to be molecularly and morphologically distinct from all other members of the genus and are described as a new species. Based on more than 9 kb of multi-locus sequence data from mitochondrial and nuclear genes, Opisthotropis hanseli sp. nov. is phylogenetically recovered to be sister to O. maculosa, a species known only by its holotype specimen from northeastern Thailand. The new species differs from its congeners by having the combination of a dark dorsum with a light spot on each scale, 20 maxillary teeth, the nasal cleft extending to near suture of the first and second supralabial, and the number and arrangement of head and body scales, notably a single internasal. The monophyly of Opisthotropis is resolved by transferring O. typica from Borneo and Palawan to the genus Hydrablabes as H. typicus comb. nov.